Re-concept of Indonesian Maritime Security to Establish Indonesian Sea Power - Seno, Ario; B. Ponto, Soleman (Forschungsforum Law Journal, 2025)
There are still some tangible maritime security threats in Indonesia national ideals and the President’s vision. the Law No. 32 of 2014 which gives mandate to Bakamla RI to establish security and safety patrol operation in Indonesian territorial and jurisdiction region. This research aims to discuss Bakamla failure to transform into Indonesia Coast Guard and the Indonesian maritime security is re-concepted to establish Indonesian Sea Power. By qualitative method that collect some data and information from latest news then analyzed by national constitution and theories from some experts, this research obtained two statements. Firstly, Bakamla RI has failed to transform into Indonesia Coast Guard and secondly, the Indonesian maritime security system needs to be re-concepted into coordinated multi agencies multi tasks in order to establish Indonesian Sea Power.